2020
DOI: 10.1002/2211-5463.12833
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA EGOT decreases breast cancer cell viability and migration via inactivation of the Hedgehog pathway

Abstract: The long noncoding RNA (lncRNA) Eosinophil Granule Ontogeny Transcript (EGOT) has been reported to inhibit the proliferation and migration of glioma cells, and promote the development and progression of gastric cancer through the Hedgehog (Hh) signaling pathway. This study was conducted to assess the role of EGOT in the progression of breast cancer. We observed that EGOT is significantly down‐regulated in breast cancer tissues and cell lines, and EGOT expression is negatively correlated with the Ki67 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…For example, CCL19 inhibited cell proliferation, migration, and invasion in gastric cancer by activating the CCR7/AIM2 signaling pathway, which could be a potential therapeutic approach ( 49 ). EGOT reduced the vitality and migration of breast cancer cells by inactivating the Hedgehog pathway ( 50 ). COL17A1 as a target of p53 can also inhibit the migration and invasion of breast cancer cells ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, CCL19 inhibited cell proliferation, migration, and invasion in gastric cancer by activating the CCR7/AIM2 signaling pathway, which could be a potential therapeutic approach ( 49 ). EGOT reduced the vitality and migration of breast cancer cells by inactivating the Hedgehog pathway ( 50 ). COL17A1 as a target of p53 can also inhibit the migration and invasion of breast cancer cells ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are a group of non-coding RNAs widely distributed in humans ( 23 ), which are different from linear non-coding RNAs such as miRNAs. It has been reported that lncRNAs may mediate upregulation or downregulation of gene expression ( 24 ), and lncRNAs are stable and widely expressed in many tumor tissues ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are a group of noncoding RNAs widely distributed in humans (19) which are different from linear noncoding RNAs such as miRNAs. It has been reported that lncRNAs may mediate upregulation or downregulation of gene expression and, despite being classified as noncoding, may also encode proteins (20).…”
Section: Discussionmentioning
confidence: 99%